Valuing transgenic drought tolerant canola using real options. Issue 3 (3rd April 2019) - Wynn, Katherine; Spangenberg, German; Smith, Kevin F.; Wilson, William
ABSTRACT: Building on the application of real options to value research and development (R&D) investment, this paper extends the application to value new canola varieties still being developed using gene technology in Australia. In this study we develop an economic model using real options and Monte Carlo simulation to estimate the ex-ante value of trait technologies under development. The model is applied to empirical field trial data for Australian canola that has been genetically modified to increase its tolerance to drought. The results show that drought tolerant canola is more profitable for farmers than cropping with conventional canola. The results also quantitatively demonstrate why breeding for drought tolerance as it is often defined, with a yield deficit under average rainfall conditions, is an unattractive investment, and why a yield advantage across rainfall levels is necessary for the trait to have market value. Investment analysis and planning is at the core of agricultural strategy and it is difficult but essential to be able to evaluate R&D investments while they are still in development. This paper contributes to that cause by demonstrating how real options can be used to value a live investment in gene technology.